2015
DOI: 10.14483/udistrital.jour.calj.2015.2.a10
|View full text |Cite
|
Sign up to set email alerts
|

Chilean 12th graders’ Attitudes towards English as a Foreign Language

Abstract: <p>This article aims to provide the results of a research focusing on 12<sup>th</sup> graders’ attitudes towards English as a Foreign Language in two secondary schools in Puerto Montt, Chile. Attitude towards a language has been considered as an important factor that influences the process of learning a foreign language (Shams, 2008); for this reason, it is fundamental to identify students’ attitudes since positive attitudes towards English allow the students to have favourable orientation to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 13 publications
6
9
0
Order By: Relevance
“…However, this study found a lack of English instruction offered to the students. This finding supported those of Burgos and Pérez (2015), Nduwimana (2019), and Silalahi (2017), that despite the students' awareness of their need for more English instruction than what is offered by their educational institutions, the exposure to English that they have got during their learning process is considered not sufficient enough to make them qualified in English. This is really the case in this research context since in most universities and colleges in Indonesia, English subject is taught only as a general subject weighted two or four credits with no follow up as specified in the curriculum.…”
Section: General Attitude Towards Studying Englishsupporting
confidence: 70%
See 1 more Smart Citation
“…However, this study found a lack of English instruction offered to the students. This finding supported those of Burgos and Pérez (2015), Nduwimana (2019), and Silalahi (2017), that despite the students' awareness of their need for more English instruction than what is offered by their educational institutions, the exposure to English that they have got during their learning process is considered not sufficient enough to make them qualified in English. This is really the case in this research context since in most universities and colleges in Indonesia, English subject is taught only as a general subject weighted two or four credits with no follow up as specified in the curriculum.…”
Section: General Attitude Towards Studying Englishsupporting
confidence: 70%
“…The data were collected through a questionnaire aimed at measuring the students' attitudes towards EFL learning in response to Industry 5.0 in Indonesia. The questionnaire was developed based on an analysis of other instruments used to identify attitudes towards EFL (Abidin, Pour-Mohammadi, & Alzwari, 2012;Burgos & Pérez, 2015) and had been contextualized to Indonesian context as well as the rise of Industry 5.0. In order to measure the internal reliability level of the questionnaire items, this instrument was tried out to 15 students who were randomly selected from the target population who did not take part in the study.…”
Section: Instrumentsmentioning
confidence: 99%
“…However, specific guidelines in the national curriculum prompt teachers to focus on providing a great deal of information to be read and listened to by learners, which reduces their opportunities to produce language. In addition, national and international proficiency test results show that Chilean learners are lagging behind their Latin American counterparts (Gómez & Pérez, 2015). In 2018, Education First reported that Chile ranked 46 out of 88 countries/ regions in the world in a language test, a ranking which belongs to the "low level" proficiency band.…”
Section: Background Of the Studymentioning
confidence: 99%
“…In the Chilean public high school context, teachers tend to deliver their l2 lessons by using l1, particularly with those learners who seem to lack commitment. Indeed, research in the Chilean high school context has suggested that whilst students appreciate the value of English as a global language, they do not show commitment towards learning the language at school (Gómez & Pérez, 2015).…”
Section: Context and Participantsmentioning
confidence: 99%
“…analysis. The questionnaire used for this research was compiled according to the questionnaires used for the purpose of examining attitudes towards a foreign language (Mihaljević Djigunović, 1998;Boonrangsri et al, 2004;Zainol et al, 2012;Burgos & Perez, 2015). Dörnyei and Taguchi (2010) stated that questionnaires are one of the most frequent and reliable methods for collection data in L2 research, because several types of information can be thus collected; factual information, and information about attitudes and behaviours.…”
Section: Methodsmentioning
confidence: 99%